Zusammengefasste Empfehlungen für ein körperliches Training zur Frakturprophylaxe postmenopausaler Frauen und Männer 45 Jahre und älter - von Stengel, Simon; Schöne, Daniel; Kohl, Matthias; Becker, Clemens; Gosch, Markus; Jakob, Franz; Kerschan-Schindl, Katharina; Kladny, Bernd; Lange, Uwe; Peters, Stefan; Sieber, Cornel; Thomasius, Friederike; et al. (Osteologie, 2023)
The design and implementation of promising training protocols for fracture prevention is a multi-step approach that has to consider a wide range of diverging aspects. Apart from the effectiveness as such, a large number of individual, logistical and financial aspects have to be taken into account to generate ideally persistantly applicable exercise training programs. Applying a sport scientific approach, the definition of dedicated training aims, based on the individual fracture risk profile, is the first step of the training process. The appropriate selection of training content and types along with training tools and methods that best possibly address the defined training aim(s) should also consider the (fracture) risk profile, health status and predispositions of the individual. Since training programs should be maintained as long as possible, ideally for life, particular attention should be paid to training principles (e. g. progressive overload, periodization), something often overlooked in scientific studies of limited duration. Summing up the applicability of exercise programms for fracture prevention, in view of the large variaty of training options and technologies, exercise is a feasible and promizing therapy for most if not all cohorts at risk for fractures - individually adjustable relating to functional status, health issues and potential contraindications. With the exception of structures for fall prevention programs as an individual home-based approach, health care systems already provide closely supervised, qualified and co-financed training programs that could be increasingly used as vehicles for fracture prevention. Unfortunately, the broad applicability of training programs on fracture prevention for almost all risk and propensity groups is often stymied by the frequently insufficient level of information of stakeholders and decision-makers regarding effectiveness, feasibility and applicability of exercise.
CRIS-Team Scopus Importer:2023-09-22
Keywords: contraindications; exercise training; fracture prevention; recommendations; setting